(untitled) (Swiss Medical Weekly, 2016)
QUESTION UNDER STUDY: In Switzerland, vaccination against varicella is not recommended in the basic immunisation schedule. However, for individuals aged 11–40 years who do not have a reliable varicella history the Swiss Federal Office of Public Health recommends either (i) a vaccination or (ii) a serology test and vaccination of those with a negative result. In the Travel Clinic of the University of Zurich, the second strategy is followed. In this study we retrospectively assessed the overall percentage of individuals with varicella-specific antibodies despite a negative history and we examined the influence of age, number of siblings, order of siblings, age difference to siblings and nationality on varicella seropositivity. METHODS: Between December 2008 and August 2015, the sera of 1757 individuals with a negative varicella history were tested for varicella antibodies. RESULTS: A total of 1593 individuals (91%) had a positive result. We found an increasing trend for varicella seropositivity with increasing age. Those aged less than 40 years were significantly more often seronegative (9.5%) than those aged 40 years and above (6.0%, p = 0.049). Seropositivity was associated with nationality. The percentage of seropositives increased with the number of siblings. CONCLUSIONS: Our results indicate that, despite the significant varicella seropositivity differences between those aged below and above, the age of 40 may not be an ideal threshold for performing a varicella serology in individuals with a negative or unknown varicella history. In the age groups above 40, testing for varicella antibodies may be especially reasonable in individuals with no or a small number of siblings and in those of specific nationalities.